2009
DOI: 10.1089/hum.2008.134
|View full text |Cite
|
Sign up to set email alerts
|

let-7 MicroRNA Transfer in Pancreatic Cancer-Derived Cells Inhibits In Vitro Cell Proliferation but Fails to Alter Tumor Progression

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is still the fourth leading cause of cancer-related deaths in Western countries, with increasing incidence. Neither effective prognostic markers nor therapies exist for this cancer. MicroRNAs are potent inhibitors of protein translation, and aberrantly expressed in many cancers. Because let-7 microRNA targets the K-ras oncogene, we aimed to characterize let-7 expression and function in PDAC in vitro and in vivo. Let-7 expression was quantified by real-time RT-PCR from re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
110
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(120 citation statements)
references
References 40 publications
8
110
0
2
Order By: Relevance
“…A number of experimental investigations have shown the tumor growth suppression effect of the Let-7 Let-7 and KRAS in colorectal cancer miRNA. [8][9][10][20][21][22] Therefore, it is not surprising that in vivo, Let-7 and Let-7 regulators may show an effect on clinical outcomes as recently found in patients with oral 13 and lung cancer. 23 Notably, the influence of the LCS6 variant on PFS and OS was present in the 55 unresponsive patients who were carriers of a KRAS mutation.…”
Section: Let-7 and Kras In Colorectal Cancermentioning
confidence: 84%
“…A number of experimental investigations have shown the tumor growth suppression effect of the Let-7 Let-7 and KRAS in colorectal cancer miRNA. [8][9][10][20][21][22] Therefore, it is not surprising that in vivo, Let-7 and Let-7 regulators may show an effect on clinical outcomes as recently found in patients with oral 13 and lung cancer. 23 Notably, the influence of the LCS6 variant on PFS and OS was present in the 55 unresponsive patients who were carriers of a KRAS mutation.…”
Section: Let-7 and Kras In Colorectal Cancermentioning
confidence: 84%
“…A preclinical in vivo experiment has been described, according to Oncogenic Anti-miRNA Significant increase in cell apoptosis [71] miR-21/mir-221 Oncogenic ASO Increases cell apoptosis/cell cycle arrest [92] miR-21 Oncogenic HIV-1-based lentiviral vectors Inhibits pancreatic cancer tumor growth both in vitro and in vivo [104] miR-27a Oncogenic Anti-miRNA Suppresses growth, colony formation and migration [105] miR-371-5p Oncogenic Anti-miRNA Proliferative inhibition [106] miR-21/miR-23a/miR-27a Oncogenic Anti-miRNA Synergistic effects in reducing cell proliferation both in vivo and in vitro [107] miR-200 and let-7 families Downregulated in gemcitabineresistant cells miRNA mimic or isoflavone Reversal of EMT phenotype leading to epithelial morphology [26] ↑ miR-22 and ↓ miR-199a -miRNA mimic or curcumin Suppressed expression SP1 transcription factor and ESR1 [60] Let-7 Tumor suppressor Plasmid-based synthetic miRNAs or by lentiviral transduction Strongly diminishes cell proliferation [108] miR-34a Tumor suppressor Lentiviral system Inhibits clonogenic cell growth and invasion and induces apoptosis and cell cycle arrest at G1 and G2/M phase [27] miR-217 Tumor suppressor miRNA-expressing plasmids Suppresses tumor cell growth in vivo [36] miR-20a Tumor suppressor Lentiviral system Inhibits proliferation and metastasis [65] miR-96 Tumor suppressor miRNA mimic and miRNA-expressing plasmid…”
Section: Manipulation Of Mirna Expression Levels As a Therapeutic Strmentioning
confidence: 99%
“…Our group extensively demonstrated the efficacy of lentiviral-based vectors to transduce and kill PDAC cells both in vitro and in vivo. 10,12,13,33 However, despite recent advances in lentiviral-based ex vivo therapeutic gene delivery in patients suffering from monogenic diseases, [14][15][16][17][18] the use of HIV as the origin of a vector system for in situ and in vivo cancer gene therapy is still surprisingly controversial. This is probably because of the pathogenic nature of the wild-type virus itself, but also to the inherent property of LVs to affect the host genome.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] However, the low efficacy of gene transfer using PEI, 5,7 the inherent immunogenic-ity of adenovirus, 8 and the manufacturing hurdles of SV40 vectors 9 challenge the use of these delivery vehicles in clinical trials. On the other hand, we recently found that lentiviral vectors (LVs) demonstrated the highest efficacy and reliability to inhibit PDAC cell proliferation both in vitro and in vivo, [10][11][12][13] and elected LVs as promising gene delivery vectors for PDAC gene therapy. However, despite successful lentiviral-based gene therapy applications in patients after infusion of corrected cells, [14][15][16][17] and more recently, after direct intracranial gene transfer, 18 the risk of insertional mutagenesis and subsequent malignant transformation of transduced cells, 19 historically demonstrated in patients during the X-SCID trial using gamma-retroviral vectors, continue to hinder the development of other integrating vectors such as LVs for in situ and in vivo cancer gene therapy, including PDAC.…”
mentioning
confidence: 99%